JOB SHOP SCHEDULING PROBLEM DENGAN ARTIFICIAL IMMUNE SYSTEM - Ericko Satyagraha; Lely Hiryanto; Gunadi Gan (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
The designed system is a job shop scheduling system using Artificial Immune System (AIS). This system will process each n jobs and every m machines in order to obtain a production schedule that has the smallest total processing time of production (makespans). Tests on the form that is already functioning as expected and where the influence of the size and number of iterations antibody discovery impact the best schedule. Keywords : Artificial Immune System, Antibody, Clone, Mutation, Vactination, Receptor.